Hot spot : Asia and Oceania - Fernandes, Clinton (Hot spot histories., 2008)
Provides coverage of the most critical situations and explosive events in the region, including internal strife in Indonesia, insurgency in southern Thailand, nuclear issues in India and Pakistan, the Tibetan revolt, the Spratly Islands dispute, and terrorist organizations such as Abu Sayeff.